Adult Born Periglomerular Cells of Odorant Receptor Specific Glomeruli - Maier, Anna-Maria; Breer, Heinz; Strotmann, Jörg (Frontiers in Neuroanatomy, 2018)
The OR37 subsystem is characterized by a variety of unique features. The odorant receptors (ORs) of this subfamily are selectively tuned to specific ligands which are supposed to play a role in social communication. OR37 expressing sensory neurons project their axons to a single receptor specific glomerulus per bulb which have been shown to be unusually stable in size and to possess a distinct repertoire of periglomerular cells. Since the neuronal network surrounding glomeruli is typically modified by the integration of adult born neurons, in this study it was investigated whether the number of adult born cells might be different for OR37 glomeruli compared to other OR-specific glomeruli. Towards this goal, 23 days after BrdU injection, BrdU labeled cells in the proximity of OR37A glomeruli as well as around OR18-2 and OR256-17 glomeruli were determined. It was found that the number of BrdU labeled cells in the periglomerular region of OR37A glomeruli was significantly lower compared to glomeruli of the other OR types. This finding was in line with a lower number of neuroblasts visualized by the marker protein doublecortin. Double labeling experiments for BrdU and marker proteins revealed that despite a relatively high number of calretinin expressing cells at the OR37A glomeruli, the number of cells co-stained with BrdU was quite low compared to other glomeruli, which may point to an individual turnover rate of this cell type for different glomeruli. Together, the results of the present study support the notion that the neuronal network at the OR37 glomeruli is less dynamic than that of other glomerulus types. This indicates a specific processing of social information in OR37 glomerular networks.